The Childfree Phenomenon: An Examination of the Interplay Between Traditional and Religious Values in the Malay Community of Jambi - Yuli, Yuliatin; Ardian, Ardian Kurniawan; Kamal, M. Kamal Fathoni (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2025)
Problem statement: This study examines the responses of the Melayu Jambi community to the concept of being childfree, which refers to the intentional decision not to have children. This phenomenon prompts significant reflection on cultural norms, Islamic beliefs, and familial regulations. Objective: The research aims to understand how the rejection of the childfree concept influences the community's perspectives on tradition and religion. Methods: Employing a qualitative approach, the study utilises in-depth interviews and content analysis involving participants from the Melayu Jambi society, including religious and traditional leaders. Results: The findings highlight a pronounced rejection of the childfree perspective, with certain respondents emphasising the significance of familial values, lineage, and the responsibilities of parenthood as outlined by Islam, which form the foundation of Melayu Jambi's heritage. In terms of the interpretation of Islamic family law, this rejection arises from the belief that parenthood constitutes an essential aspect of a Muslim's responsibilities and obligations. Furthermore, this opposition reflects concerns regarding the long-term implications of the childfree ideology on families and communities. Conclusion: The study provides insights into the complexities of a society that dismisses the childfree concept as an effort to uphold enduring traditional and religious principles. It serves as a reflection of values that illustrate how this opposition signifies the community's aspiration to maintain steadfast views on family and parental roles in the face of evolving cultural and societal changes.